Lebesgue Integral Inequalities of Jensen Type for λ-Convex Functions - Dragomir, Silvestru Sever (Armenian Journal of Mathematics, 2022)
Some Lebesgue integral inequalities of Jensen type for $λ$-convex functions defined on real intervals are given.